OPTIMALISASI PENERIMAAN RETRIBUSI JASA UMUM DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MALANG - Capriati, Christia (Jurnal Mahasiswa Perpajakan, 2015)
The purpose of this qualitative descriptive study is to know and explain about the public service retribution revenue as one source of Revenue in Malang Regency. It is to analyze the constraints faced in the implementation of the optimalization of the district government revenue, public services, government efforts in Malang Regency in overcoming the obstacles that is existing. Local Genuine Income (PAD) is expected to be a main support to finance local activities. Every local government works hard to improve the local economic, including the improvement of PAD. One relatively great inflow to PAD is coming from retributions. Local retributions are the source of finance for the implementation of local government and local development through which the welfare of peoples will be improved and evenly distributed throughout population. The kind of public service retributions is more variable than that of service business and permit retributions. Higher collection of retributions will increase the revenue accepted by the government. Keyword: Optimalization, Public Service Retribution, Local Genuine Income(PAD)